A Retrospective Analysis of Breast Cancer at BPKMCH, Nepal - Pun, Chin Bahadur; Shrestha, Sadina; Bhatta, Ranjan Raj; Pandey, Greta; Uprety, Suraj; Bastakoti, Shankar; Dhungana, Ishan; Jha, Nandita (Nepalese Journal of Cancer, 2020)
Introduction: Breast cancer is the most common cancer and also the leading cause of cancer related mortality in women worldwide which impact 2.1 million women each year. Breast cancer rates are increasing in nearly every region globally. Methods: This was retrospective study at Department of Pathology in B P Koirala Memorial Cancer Hospital effective from 15 April 2018 to 14 April 2019. All the data were retrieved and analyzed. Results: Total 205 breast cancer cases were analyzed, among them 198 cases were females accounting 96.5 %and 7 cases were males accounting 3.5 %.Among 205 cases, 181 (88.6%) cases were invasive ductal Carcinoma No Special Type. Majority of cases 111(54%) were diagnosed with Nottingham grading system grade II of breast cancer. According to our study breast cancer was most common in the age group 41-50 years (32.2%). Conclusion: Breast cancer is more common in females than in males. Most common affected age group was 41-50 years. Most common histological type was invasive ductal carcinoma NST. Similarly, left sided breast cancer was more common than right.